2007
DOI: 10.1177/003335490712200109
|View full text |Cite
|
Sign up to set email alerts
|

The National down Syndrome Project: Design and Implementation

Abstract: This exceptional compilation of questionnaire, clinical, and molecular data makes the NDSP a unique resource for ongoing studies of the etiology and phenotypic consequences of trisomy 21. The combined approach increases study power by defining subgroups of cases by the origin of nondisjunction. This report describes the design and successful implementation of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 14 publications
5
83
0
1
Order By: Relevance
“…Our findings confirm the model for DS origin found in other populations (Antonarakis, 1991;Gó mez et al, 2000;Petersen and Mikkelsen, 2000;Machatkova et al, 2005;Freeman et al, 2007;Ramírez et al, 2007;Ghosh et al, 2010). The obtained frequencies of maternal MIderived (86%) and MII-derived (14%) trisomy 21 were different from the study reported by Freeman et al (2007), but similar to the studies on Mediterranean and Eastern Europe populations (Gó mez et al, 2000;Machatkova et al, 2005). The discrepancy was probably due to both the small sample size and maternal age distribution covered by the study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings confirm the model for DS origin found in other populations (Antonarakis, 1991;Gó mez et al, 2000;Petersen and Mikkelsen, 2000;Machatkova et al, 2005;Freeman et al, 2007;Ramírez et al, 2007;Ghosh et al, 2010). The obtained frequencies of maternal MIderived (86%) and MII-derived (14%) trisomy 21 were different from the study reported by Freeman et al (2007), but similar to the studies on Mediterranean and Eastern Europe populations (Gó mez et al, 2000;Machatkova et al, 2005). The discrepancy was probably due to both the small sample size and maternal age distribution covered by the study.…”
Section: Discussionsupporting
confidence: 91%
“…The discrepancy was probably due to both the small sample size and maternal age distribution covered by the study. As the sample size increases, the results are more similar to that obtained by Freeman et al (2007), which included an impressive number of cases. Allen et al (2009) found that the ratio of maternal MI-to MII-derived trisomy 21 cases was less in the youngest ( < 15) and the oldest (40-50) maternal age groups compared with that in the other maternal age groups.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Shared Genetic Susceptibility-Nondisjunction, or the failure of chromosome pairs to separate properly during meiosis or mitosis, is the principal cause of Down syndrome, and is of maternal origin over 90% of the time (Freeman et al, 2007). Schupf and her associates (Schupf et al, 1994;Schupf, Kapell et al, 2001) therefore postulated that if there was a shared genetic susceptibility for Down syndrome and Alzheimer's disease, it should only be most evident among mothers and maternal relatives of individuals with Down syndrome.…”
Section: Risk Factorsmentioning
confidence: 99%